The Effect of Religiosity on Muslim Consumer’s Switching Behavior in Greater Jakarta Area - Buhari, Nadhira (APPS Publications, 2022)
Article Info: Received 14 January 2022, Accepted 10 July 2022 Article Correspondence: nadhirabuhari@gmail.com Recommended Citation: Buhari, Nadhira (2022). The Effect of Religiosity on Muslim Customer’s Switching Behavior in the Greater Jakarta Area. Journal of Multidisciplinary Issues 2(1) 10 – 17 (2022)